Gut Microbiota Modulates the Protective Role of Ginsenoside Compound K Against Sodium Valproate-Induced Hepatotoxicity in Rat - Zhou, Luping; Zeng, Xiangchang; Liao, Jianwei; Chen, Lulu; Ouyang, Dongsheng (Frontiers in Microbiology, 2022)
This study aimed to investigate the potential role of gut microbiota in the hepatotoxicity of sodium valproate (SVP) and the protective effect of ginsenoside compound K (G-CK) administration against SVP-induced hepatotoxicity in rats. Measurements of 16S rRNA showed that SVP supplementation led to a 140.749 and 248.900-fold increase in the relative abundance of Akkermansia muciniphila (A. muciniphila) and Bifidobacterium pseudolongum (B. pseudolongum), respectively (p <0.05). The increase in A. muciniphila was almost completely reversed by G-CK treatment. The relative abundance of A. muciniphila was strongly positively correlated with aspartate transaminase (AST) and alanine aminotransferase (ALT) levels (r >0.78, p <0.05). The PICRUSt analysis showed that G-CK could inhibit the changes of seven pathways caused by SVP, of which four pathways; including the fatty acid biosynthesis, lipid biosynthesis, glycolysis/gluconeogenesis and pyruvate metabolism; were found to be negatively correlated with AST and ALT levels (r ≥0.70, p <0.01 or <0.05). In addition, the glycolysis/gluconeogenesis and pyruvate metabolism were negatively correlated with the relative abundance of A. muciniphila (r >0.65, p <0.01 or <0.05). This alteration of the gut microbiota composition that resulted in observed changes to the glycolysis/gluconeogenesis and pyruvate metabolism may be involved in both the hepatotoxicity of SVP and the protective effect of G-CK administration against SVP-induced hepatotoxicity. Our study provides new evidence linking the gut microbiota with SVP-induced hepatotoxicity.